Mastering The Art of Speaking: Enhancing Grade 11 Students’ Speaking Skill Through Speakup Scaffold - Amer Mehmood Jason P. Ahmed; Lhea D. Ildefonso; Othaniel Lubbong; Jayson Blanza (Journal of Arts, Humanities and Social Science)
This action research examined the effect of the SpeakUp Scaffold, a guided speaking intervention, on the oral communication competencies of thirty- two Grade 11 senior high school students. The research was initiated due to ongoing speaking problems among students in the form of limited vocabulary, stage fright, fear of negative judgment, unfamiliarity with the language of English, and low self-esteem issues. The research was intended to establish the extent to which the incorporation of scaffolded speaking activities would impact students’ speaking performance and levels of anxiety. The research utilized both qualitative and quantitative data gathering instruments in the form of pre- and post-intervention speaking performance rubric, teacher observation, and student reflective journals. The four-week intervention included progressively challenging speaking exercises to improve confidence, vocabulary utilization, fluency, and coherence. The results showed that trainees' speaking abilities had significantly improved. Notably, students demonstrated better thought organization, increased use of scholarly language, and higher levels of talkativeness. Scaffolded input also assisted in curbing speaking anxiety as guided preparation, peer traffic, and explicitly organized expectations benefited the students. The research establishes the fact that scaffolded speaking activities like the SpeakUp Scaffold can be an efficient learning approach in the development of students’ oral communication skills, particularly in cases where speaking nervousness is an embedded hindrance. Recommendations are made for the integration of scaffolded speaking habits in the everyday curriculum and offering extended, structured time for students to enhance practice in using English and gaining confidence in expression.